1990
DOI: 10.1017/s0031182000079828
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the surface and cyst fluid components of Taenia crassiceps

Abstract: Information relating to the characterization of cestode surface macromolecules is limited. This is especially the case with Taenia crassiceps, a well-recognized model for the study of larval cestodiasis. Here, the protein and glycoprotein composition of the tegumental surface and cyst fluid of the metacestode have been investigated using radio-isotope labelling, immunoprecipitation, SDS-PAGE and lectin affinity chromatography. A restricted number of surface proteins was labelled with the 125I/Iodogen method al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Finally, it is known that one of the main functions of carbohydrates associated with proteins is protection of the polypeptide chain (Allen and Kisailus 1992;Montreuil 1993;Varki 1993). This would be especially important in host-parasite relationships, as has been suggested for Schistosoma mansoni (Schmidt 1995), T. crassiceps (Lamsam and McManus 1990), and T. taeniaeformis (Hammerberg et al 1980), and in this paper, preliminary data for T. solium are presented.…”
Section: Discussionmentioning
confidence: 71%
“…Finally, it is known that one of the main functions of carbohydrates associated with proteins is protection of the polypeptide chain (Allen and Kisailus 1992;Montreuil 1993;Varki 1993). This would be especially important in host-parasite relationships, as has been suggested for Schistosoma mansoni (Schmidt 1995), T. crassiceps (Lamsam and McManus 1990), and T. taeniaeformis (Hammerberg et al 1980), and in this paper, preliminary data for T. solium are presented.…”
Section: Discussionmentioning
confidence: 71%
“…On the other hand, numerous tegumental proteins lacking the DM9 motif have been identified and purified from F. gigantica (5)(6)(7)64), S. japonicum (69,70), S. mansoni (31,39,55), C. sinensis (18,74), Echinococcus granulosus (56), and Taenia spp. (40,42,54), and none of these proteins shares homology with FhTP16.5. Proteins of 50 kDa and 25 to 40 kDa have also been identified in the tegumental syncytium of various F. hepatica stages using monoclonal antibodies (2,34), but these proteins have not yet been purified and characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Aspecific reactions may reveal that these glycoconjugates are glycoproteins reacting, as endogenous lectins, with sugar moities of FITC-lectins. Lamsam & McManus (1990) suggested that T. crassiceps metacestode releases glycoproteins from its surface. Highly immunogenic carbohydrates of these glycoproteins may serve to divert the host immune response, for example by fixing complement.…”
Section: Discussionmentioning
confidence: 99%